KOMUNIKASI INTERPERSONAL GURU DAN PESERTA DIDIK DI SMP NEGERI 2 TAPALANG KECAMATAN TAPALANG KABUPATEN MAMUJU - Chuduriah Sahabuddin (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2014)
Background underlying this study is the importance of communication between teachers and learners because it has a great influence in determining the achievements of learners. The purpose of this study was to determine how the interpersonal communication of teachers and students in junior high school 2 Tapalang. This study uses peneltian procedure Ex Post Facta using descriptive research design. The research subjects are students of class IX is the number of learners 63 people and Indonesian teachers, this research instrument was Questionnaire, observation and interviews. The results showed after the total score divided by the number of respondents (3364: 63 = 53.39) the results obtained was 53.39. Thus, the average total score of 53.39 interpersonal communication teachers and students at the junior high school 2 Tapalang is high or good. Observations and interviews known that Interpersonal Communication between teachers and students in the ninth grade junior high school 2 Tapalang 2015/2016 school year in the category of good / high, so the teacher should keep the pattern of communication with students and continue to strive to establish good relationships with the students first related to communication. Teachers who do not have a pattern of good communication with students, are expected to attempt to establish communication with students more intense. Communication between teachers and students is a form of engagement of both elements in the learning process that takes place.